Using genetic algorithms to generate Ds-optimal response surface designs - Sirisom, P.; Chaimongkol, S.; Borkowski, J. J. (Lobachevskii journal of mathematics, 2014)
This research introduces a new approach to the generation of D s -optimal designs for subsets of parameters of the second-order response surface model for 2, 3, and 4-dimensional hypercube design spaces while simultaneously satisfying a specified minimum value for the D -efficiency for the full model. Specifically, 1-point and 2-point exchange algorithms and a genetic algorithmwere developed to generate these designs. The results indicate that the D s -criterion values of the GA designs were greater than or equal to those of designs generated by exchange algorithms and by the Optex procedure in SAS . Thus, in general, the GA is superior to the exchange algorithms for generating subset optimal designs.